Separate and Unequal: The Impact of Socioeconomic Status, Segregation, and the Great Recession on Racial Disparities in Housing Values. Issue 2 (April 2018) - Thomas, Melvin E.; Moye, Richard; Henderson, Loren; Horton, Hayward Derrick
The effects of race, class, and residential segregation on housing values continue to be a major focus of sociological research. Nevertheless, there has yet to be a study that places these factors in the context of the great recession of 2008 and 2009. Accordingly, the purpose of this work is to assess the extent to which the great recession affected housing values for African Americans and whites relative to the joint effects of race, class, and residential segregation. The following research questions are addressed: (1) How do segregation and socioeconomic status (SES) affect racial differences in housing values? (2) What were the levels of racial disparity in housing values before, during, and after the great recession? and (3) Were the housing values of higher status African Americans insulated from the negative impact of segregation and the great recession compared with their lower status counterparts? Using the Integrated Public Use Micro-data Series, the 2010 metropolitan area dissimilarity and population density scores, and hierarchical linear modeling, the findings revealed that the great recession exacerbated racial differences in housing values most in the higher SES categories. Higher status African Americans were more disadvantaged relative to comparable whites than lower status African Americans compared with similar whites in terms of housing values. The article concludes with a discussion of the implications of the findings.